The Implementation of Coding and Artificial Intelligence: A Case Study of the ICT Zainal Abidin Elementary School Curriculum - Mahbubi, M. (Tarunateach: Journal of Elementary School, 2026)
This study examines the implementation of coding and artificial intelligence (AI) in the curriculum at SD ICT (Sekolah Dasar Information and Communication Technology)  Zainal Abidin, an elementary school in Indonesia. With the growing demand for digital literacy and technology-based competencies in the 21st century, this research aims to explore how coding and AI are integrated into the curriculum, the opportunities they offer for enhancing students' critical thinking and problem-solving skills, and the challenges encountered during implementation. Using a qualitative case study approach, data were collected through semi-structured interviews with 5 teachers and 2 school administrators, classroom observations, and analysis of curriculum documents. The interviews focused on participants' perspectives regarding the integration process, benefits, and challenges of teaching coding and AI. The collected data were analyzed using thematic analysis to identify key themes related to the integration of these subjects. The findings suggest that integrating coding and AI into the curriculum provides valuable opportunities for students to develop computational thinking, creativity, and a deeper understanding of technology. However, the research also identifies several challenges, including insufficient teacher training, limited infrastructure, and alignment issues with the national educational framework. The study highlights the importance of professional development for teachers, better resource allocation, and curriculum adjustments to ensure the sustainable integration of coding and AI in primary education. Recommendations are made for educators and policymakers to enhance the effectiveness of this integration to prepare students for a digital future better.